Lipid profile analysis of donkey milk during the lactation - Du, Xinyi; Ma, Zongjie; Wang, Changfa; Zhou, Miaomiao (Frontiers in Nutrition, 2025)
IntroductionFrom ancient times, donkey milk (DM) has attracted much attention due to its particular properties. Donkey milk is characterized by a high level of lactose and low levels of protein and fat. However, studies investigating lipid changes in DM during lactation are limited.MethodsThe lipid profile of DM at different lactation stages was analyzed using lipidomics in this study. Milk samples were collected from six lactating Dezhou donkeys on days 1, 30, 60, 90, 120, 150, and 180 of lactation.ResultsA total of 1,552 lipids were identified, belonging to 5 major categories and 21 subclasses. Glycerophospholipids (GP, 62.11%) and sphingolipids (SP, 22.94%) were the predominant categories. At the subclass level, phosphatidylcholine (PC, 27.26%), phosphatidylethanolamine (PE, 17.59%), and phosphatidylserine (PS, 6.77%) were the most abundant lipids. Significant variations in the levels of GP, SP, glycerolipids (GL), and free fatty acids (FA) were observed across lactation stages. Colostrum was rich in GP and SP, whereas mature milk contained more GL. Regarding FA, mature milk had a higher content of linolenic acid than colostrum, while colostrum was richer in carnitines. Fourteen lipids were identified as potential biomarkers for distinguishing between DM from different lactation stages.DiscussionThese results indicate that the lactation stage significantly affects the lipid composition of DM. This study provides a detailed lipidomic profile of DM, which will facilitate its further development and utilization.